2015
DOI: 10.4081/jae.2015.449
|View full text |Cite
|
Sign up to set email alerts
|

The influence on biogas production of three slurry-handling systems in dairy farms

Abstract: Handling systems can influence the production of biogas and methane from dairy farm manures. A comparative work performed in three different Italian dairy farms showed how the most common techniques (scraper, slatted floor, flushing) can change the characteristics of collected manure. Scraper appears to be the most neutral choice, as it does not significantly affect the original characteristics of manure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Methane yield resulted in 87. 4 The biogas yield of grass was higher than expected, similar to the yield from energy crops, especially in terms of NL•kg −1 VS [33,34]. Other authors reported BMP values of 337 NL•kg −1 VS for a mixture of switchgrass and swine manure without assessing the specific yield from grass [26].…”
Section: Biogas Production and Yieldmentioning
confidence: 78%
See 2 more Smart Citations
“…Methane yield resulted in 87. 4 The biogas yield of grass was higher than expected, similar to the yield from energy crops, especially in terms of NL•kg −1 VS [33,34]. Other authors reported BMP values of 337 NL•kg −1 VS for a mixture of switchgrass and swine manure without assessing the specific yield from grass [26].…”
Section: Biogas Production and Yieldmentioning
confidence: 78%
“…Methane yield resulted in 87. 4 (Figure 6). Results can be considered comparable, despite the higher production that was achieved, in reference to wet mass and TS, for summer grass and for spring grass in reference to VS.…”
Section: Biogas Production and Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…For AD, that is a continuous process, and this presents a barrier to more widespread adoption. As manure-based AD captures most CH 4 and achieves the best environmental outcome when fed regularly on fresh manure that has not had time to degrade [22,23], it would not be efficient to store winter-produced slurry for use during the grazing season. Therefore, the potential size of any system on a pasture farm will be limited by the availability of slurry collected during the grazing season, unless another feedstock is available.…”
Section: Anaerobic Digestionmentioning
confidence: 99%
“…The primary sector can play a significant role to reach the goals of sustainable development and circular economy by the exploitation of wastes or by-products for the production of renewable energy [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%